2021
DOI: 10.1021/acs.jafc.1c01651
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Novel Isothiazole-Purines as a Pyruvate Kinase-Based Fungicidal Lead Compound

Abstract: Target identification is one of the most important bases for novel pesticide development; pyruvate kinase (PK) was discovered as a potent fungicide target in our previous studies. To continue the PK-based fungicide development, novel isothiazolepurine derivatives were rationally designed and synthesized. Bioassay results showed that compound 5ai displayed excellent in vitro activity against Rhizoctonia solani with an EC 50 of 1.5 μg/mL, which was superior to those of positive controls diflumetorim with its EC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Therefore, exploration and validation of molecular targets have become critical milestones before target-based molecular designs can be realized. 25 Recent studies suggested that insect chitinases could be used as a promising potential insecticide target, 26,27 and transketolases could be used as a promising potential herbicide target. 28 In addition, a highly active fungicidal lead YZK-C22, 3-(4-methyl-1,2,3-thiadiazol-5-yl)-6-(trichloromethyl)- [1,2,4]-triazolo- [3,4-b][1,3,4]-thiadiazole (Figure 1), was discovered 29 by inhibiting the fungal pyruvate kinase (PK).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, exploration and validation of molecular targets have become critical milestones before target-based molecular designs can be realized. 25 Recent studies suggested that insect chitinases could be used as a promising potential insecticide target, 26,27 and transketolases could be used as a promising potential herbicide target. 28 In addition, a highly active fungicidal lead YZK-C22, 3-(4-methyl-1,2,3-thiadiazol-5-yl)-6-(trichloromethyl)- [1,2,4]-triazolo- [3,4-b][1,3,4]-thiadiazole (Figure 1), was discovered 29 by inhibiting the fungal pyruvate kinase (PK).…”
Section: ■ Introductionmentioning
confidence: 99%
“…A fungicidal lead [3-(4-methyl-1,2,3-thiadiazol-5-yl)-6-(trichloromethyl)-[1,2,4]-triazolo­[3,4- b ]-[1,3,4]­thiadiazole] ( YZK-C22 ) targeting pyruvate kinase (PK) was discovered in our previous study using drug affinity reaction target stability (DARTS) against Saccharomyces cerevisiae, and its mode of action was further validated by the corresponding enzymatic studies. , Afterward, its mode of action was further validated in the Botrytis cinerea system . In addition, a few chemical scaffolds such as isothiazopurines, triazolothiadiazines, and psoralen-based 1,3,4-oxadiazoles were successfully discovered as PK inhibitors by computer-aided molecular design technology. These findings expanded the structural diversity of PK inhibitors and laid a foundation for further structural optimization of PK inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…16−20 Based on homology modeling and computer-aided pesticide design techniques, our team successfully designed and synthesized a series of novel isothiazolopurine derivatives; we discovered a highly potent compound [i.e., 8-(3,4dichloroisothiazol-5-yl)-9-ethyl-N-(4-methoxybenzyl)-9Hpurin-6-amine] targeting PK. 21 Previous results described above indicated that PK can be an effective target for further novel fungicide development.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PK is widely present in animals, plants, microorganisms, and cultured cells to catalyze the transformation of phosphoenolpyruvate (PEP) to pyruvate in the last step of glycolysis. It is an essential enzyme for adenosine triphosphate (ATP) production and cell metabolism regulation in all organisms. Based on homology modeling and computer-aided pesticide design techniques, our team successfully designed and synthesized a series of novel isothiazolopurine derivatives; we discovered a highly potent compound [i.e., 8-(3,4-dichloroisothiazol-5-yl)-9-ethyl- N -(4-methoxybenzyl)-9 H -purin-6-amine] targeting PK . Previous results described above indicated that PK can be an effective target for further novel fungicide development.…”
Section: Introductionmentioning
confidence: 99%